Faktor Penyebab Kesulitan Siswa dalam Memecahkan Masalah Geometri Materi Bangun Datar - Dwi Laila Sulistiowati (CV. Multi Kreasi Media, 2022)
This research is motivated by the difficulties experienced by students in solving geometric problems. The purpose of this study was to analyze the factors that cause students' difficulties in solving geometric problems. This type of research is a qualitative descriptive research. The subjects in this study were 38 grade VIII students of junior high school. The research instruments used were problem-solving ability tests, interview guidelines, and observation sheets. The results showed that the factors that caused students to experience difficulties in solving geometry problems consisted of internal and external factors. Internal factors come from within the students, including inaccuracy, lack of understanding of mathematical concepts related to problems, and students' geometric skills. Meanwhile, internal factors come from outside the students themselves, namely from educators and the learning process carried out.